El Excentrico, 1953-10-20 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
October 20, 1953 [20 de octubre de 1953]. Ano 3, No. 24. Cover has photos of performer Pedro Infante and his Mariachis Vargas de Tecalitlan. This cover serves as a flyer encouraging viewers to be at their live performance that took place five days after this issue's release at the Civic Auditorium. The headline reads, "Frank Davilla presents...En persona Pedro Infante y el Mariachi Vargas de Tecalitlan."